Manufacturing method of hydrated solidified bodies

JP7652144B2Active Publication Date: 2025-03-27JFE STEEL CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022114598
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-07-19
Publication Date
2025-03-27
Estimated Expiration
2042-07-19

Smart Images

  • Figure 0007652144000001
    Figure 0007652144000001
  • Figure 0007652144000002
    Figure 0007652144000002
Patent Text Reader

Abstract

To obtain a hydrated solidified body having excellent durability.SOLUTION: A method for producing a hydrated solidified body includes kneading and hardening a composition containing an aggregate containing a steel slag, a binder containing a blast furnace slag fine powder and water to obtain a hydrated solidified body. The steel slag includes steel slag fine aggregate which is a fine aggregate. The steel slag fine aggregate has a calcium ion concentration of 30 mg / L or more, in a test solution obtained by conducting a "Test by use as it is" as described in JIS K 0058-1:2005 "Test Methods for Chemical Substances in Slags - Part 1: Method for Testing Elution Amount"; and a mixing amount of the steel slag fine aggregate is 800 kg / m3 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a hydrated solidified material. [Background technology]

[0002] 2. Description of the Related Art Hydrated solids such as concrete and mortar are conventionally known. Hydrated solids are generally obtained by kneading and hardening a composition containing aggregates of different particle sizes (fine and coarse aggregates) such as natural crushed stone or mountain sand, a binder that hardens through a hydration reaction such as cement, and water. As such a hydrated solidified material, a hydrated solidified material using aggregate containing steelmaking slag (hereinafter also referred to as "steelmaking slag hydrated solidified material") is known (Patent Document 1), and is used as a port civil engineering material, roadbed material, etc. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-264045 A Summary of the Invention [Problem to be solved by the invention]

[0004] Hydrated concrete using steel slag may have a smaller static elastic modulus than concrete with the same compressive strength. In this case, the hydrated concrete will have larger drying shrinkage and creep deformation, resulting in poor durability.

[0005] Therefore, an object of the present invention is to obtain a hydrated solidified material having excellent durability. [Means for solving the problem]

[0006] The present inventors have found that the above object can be achieved by employing the following configuration, and have completed the present invention.

[0007] That is, the present invention provides the following [1] to [5]. [1] A hydrated solidified body is obtained by kneading and hardening a composition containing an aggregate containing steelmaking slag, a binder containing ground granulated blast furnace slag, and water, and the steelmaking slag contains a fine aggregate, which is a steelmaking slag fine aggregate, and the calcium ion concentration in the test solution obtained by carrying out a "test in the form of use" described in JIS K 0058-1:2005 "Testing methods for chemical substances of slags - Part 1: Testing methods for elution amount" is 30 mg / L or more, and the mixing amount of the steelmaking slag fine aggregate is 800 kg / m 3 This is the above method for producing a hydrated solidified body. [2] The method for producing a hydrated solid described in [1] above, wherein the mass ratio of the fine steelmaking slag aggregate to the ground granulated blast furnace slag is 2.0 or more. [3] The method for producing a hydrated solidified body according to the above [1] or [2], wherein the binder further contains cement. [4] The method for producing a hydrated solidified material according to any one of the above [1] to [3], wherein the obtained hydrated solidified material is crushed to 2000 kg / piece or less. [5] The method for producing a hydrated solidified material according to any one of the above [1] to [4], wherein the obtained hydrated solidified material is crushed to a particle size of 53 mm or less. Effect of the Invention

[0008] According to the present invention, a hydrated solidified material having excellent durability can be obtained. The hydrated solidified material, which has excellent durability, can be used, for example, as a substitute for natural stone or concrete, as rubble or roadbed material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Findings Obtained by the Inventors] The structure of a hydrated solidified body using steelmaking slag as an aggregate is roughly divided into a paste phase composed of water and a binder such as ground granulated blast furnace slag, and an aggregate phase composed of steelmaking slag.

[0010] The compressive strength of the hydrated solid can be controlled by the water-binder ratio (mass ratio of water to binder), and is generally 18 to 50 N / mm 2 The strength of concrete is about the same as that of ordinary concrete. As the compressive strength increases, the static elastic modulus also increases. The static elastic modulus of ordinary concrete is 20N / mm 2 When the load is about 23kN / mm 2 , compressive strength is 35N / mm 2 When the load is about 30kN / mm 2 , compressive strength is 50N / mm 2 Approximately 33kN / mm 2 It is. On the other hand, the static elastic modulus of the hydrated solidified material is 20N / mm 2 When the load is 16~22kN / mm 2 , compressive strength is 35N / mm 2 When the load is 24~30kN / mm 2 , compressive strength is 50N / mm 2 When the load is about 28~33kN / mm 2 It is. In other words, the static elastic modulus of the hydrated concrete is smaller than or equal to that of ordinary concrete with the same compressive strength.

[0011] The inventors have found that the compressive strength at 28 days is approximately 35 N / mm 2 The drying shrinkage and creep deformation of the hydrated solidified bodies (hydrated solidified bodies A and B) and ordinary concrete were investigated. The static elastic modulus of hydrated solidified material A is 24 kN / mm 2 The strength of the hydrated solidified material B and ordinary concrete was 30 kN / mm 2 It was. As a result of the investigation, it was found that hydrated solidified material A, which has a small static elastic modulus, had greater drying shrinkage and creep deformation than hydrated solidified material B, which has a large static elastic modulus, and ordinary concrete. Therefore, if the static elastic modulus of the hydrated solid can be increased, durability equivalent to that of ordinary concrete can be obtained.

[0012] In the past, the factors governing the static elastic modulus of hydrated soils were unclear and could not be controlled. Therefore, the present inventors have investigated the effects of the components and mixing conditions used on the static elastic modulus of the hydrated solidified material. As a result, the inventors found that the amount of calcium ions dissolved from and the blending amount of steelmaking slag equivalent to fine aggregate (roughly speaking, steelmaking slag with a particle size of 5 mm or less) affect the static elastic modulus.

[0013] The reason for this is not clear, but is thought to be as follows. That is, calcium ions from the steelmaking slag equivalent to fine aggregate dissolve into the paste phase (ground granulated blast furnace slag and water), causing a hydration reaction between the paste phase and the calcium ions. As a result, a strong transition zone is formed at the interface between the aggregate phase (steelmaking slag) and the paste phase, and the aggregate phase and the paste phase are firmly bonded together. This improves the static elastic modulus of the hydrated solidified body.

[0014] In this case, if the particle size of the steelmaking slag is too large (i.e., if the steelmaking slag is not fine aggregate), the contact area between the aggregate phase and the paste phase is small, so even if a large amount of calcium ions are dissolved, the effect will be limited. Furthermore, if the amount of steelmaking slag equivalent to fine aggregate is too small, the total contact area between the aggregate phase and the paste phase becomes small, and the effect is also limited.

[0015] The present invention has been made based on the above findings. Hereinafter, one embodiment of the present invention will be described in detail.

[0016] [Manufacturing method of hydrated solidified bodies] The method for producing a hydrated solidified body of this embodiment (hereinafter also referred to as "this production method") is, in outline, a method for obtaining a hydrated solidified body by kneading and hardening a composition containing aggregate containing steelmaking slag, a binder containing ground granulated blast furnace slag, and water. This manufacturing method will now be described in detail.

[0017] <aggregate> First, the aggregate used in this manufacturing method will be described.

[0018] Steel Slag The aggregate includes steel slag. Examples of steelmaking slag include slag generated in converters, electric furnaces, and torpedo cars (e.g., converter decarburization slag); hot metal pretreatment slag; and slag generated during stainless steel refining, with a T.Cr content of 0.5% by mass or more. Steelmaking slag that has been aged can also be used, and preferred examples include slag with a water immersion expansion ratio of 0.5% or less. Although this increases the cost, steelmaking slag that has been air-crushed may be used as part of the steelmaking slag.

[0019] (Fine steel slag aggregate) At least a portion of the steel slag is fine aggregate. As described in JIS A 0203:2014 "Concrete Terminology", fine aggregate is aggregate that passes entirely through a 10 mm mesh sieve and at least 85% of it passes through a 5 mm mesh sieve by mass. Hereinafter, steelmaking slag, which is a fine aggregate, may be referred to as "steelmaking slag fine aggregate."

[0020] (Calcium ion concentration) First, in the following, the calcium ion concentration in the test solution obtained by performing the "As-used test" described in JIS K 0058-1:2005 "Testing methods for chemical substances of slags - Part 1: Testing method for leaching amount" may be simply referred to as the "calcium ion concentration".

[0021] The steelmaking slag fine aggregate used in this manufacturing method has a calcium ion concentration of 30 mg / L or more. Such steelmaking slag fine aggregate has a large amount of calcium ion elution. Therefore, as described above, the obtained hydrated body has an improved ratio of static elastic modulus to compressive strength (static elastic modulus / compressive strength) and is excellent in durability.

[0022] In addition, two or more types of steel slag as fine aggregate may be used in combination. In this case, for example, if a material with a calcium ion concentration of 30 mg / L or more is mixed with a material with a calcium ion concentration of less than 30 mg / L, and the mixture has a calcium ion concentration of 30 mg / L or more, the mixture is considered to be the steelmaking slag fine aggregate used in this manufacturing method.

[0023] Because the durability of the resulting hydrated solidified body is superior, the calcium ion concentration of the steelmaking slag fine aggregate is preferably 50 mg / L or more, more preferably 70 mg / L or more, even more preferably 90 mg / L or more, particularly preferably 110 mg / L or more, and most preferably 130 mg / L or more.

[0024] On the other hand, from the viewpoint of reducing the elution of alkaline components from the obtained hydrated solidified body, the calcium ion concentration of the steelmaking slag fine aggregate is preferably 900 mg / L or less, more preferably 700 mg / L or less, and even more preferably 500 mg / L or less.

[0025] ((Amount)) The mixing ratio of steel slag fine aggregate is 800kg / m 3 As a result, as described above, the obtained hydrated solidified material has an improved ratio of static elastic modulus to compressive strength (static elastic modulus / compressive strength) and is excellent in durability. The amount of fine steel slag aggregate mixed is set at 2000 kg / m because the resulting hydrated solidified body has better durability. 3 Less than 1500kg / m is preferable. 3 Less than 1000kg / m is more preferable. 3 The following is even more preferred:

[0026] In order to form a strong transition zone at the interface between the aggregate phase (steel slag) and the paste phase, the mixing ratio of fine steel slag aggregate is set at 900 kg / m 3 More than 1000kg / m is preferable. 3 More preferably, 1100kg / m 3 More preferably, 1200 kg / m 3 The above is particularly preferred.

[0027] (Steel slag coarse aggregate) In this manufacturing method, as the steelmaking slag, not only fine aggregate (steelmaking slag fine aggregate) but also coarse aggregate may be used. As described in JIS A 0203:2014 "Terminology for Concrete", coarse aggregate is aggregate of which 85% or more by mass remains on a 5 mm mesh sieve. Hereinafter, steelmaking slag, which is a coarse aggregate, may be referred to as "steelmaking slag coarse aggregate." The mixing ratio of steel slag coarse aggregate is 50kg / m 3 More than 150kg / m is preferable. 3 More preferably, 300 kg / m 3 More preferably, 700 kg / m 3 The above is particularly preferred. On the other hand, the mixing ratio of steel slag coarse aggregate is 1400kg / m 3 Less than 1200kg / m is preferable. 3 The following is more preferred:

[0028] (Surface dry density) In this manufacturing method, the surface dry density of the steelmaking slag used is 2.8 g / cm 3 More than 3.0 g / cm is preferable. 3 The above is more preferable. On the other hand, the surface dry density of steelmaking slag is 4.0 g / cm 3 Less than 3.8 g / cm is preferred. 3 The following is more preferred: The surface dry density of steelmaking slag is determined in accordance with the methods described in JIS A 1109:2020 "Test methods for density and water absorption of fine aggregate" and JIS A 1110:2020 "Test methods for density and water absorption of coarse aggregate".

[0029] Other bones In the present production method, other aggregates may be used, for example, natural crushed stone, mountain sand, slowly cooled blast furnace slag, granulated blast furnace slag, recycled aggregate for concrete, and the like. However, from the viewpoint of effective utilization of steelmaking slag, the volume ratio (volume ratio) of steelmaking slag in the aggregate is preferably 50 volume % or more, more preferably 75 volume % or more, and even more preferably 100 volume %.

[0030] <Binding material> The binder is a component that hardens through a hydration reaction. The total amount of binder is 250kg / m 3 More than 300kg / m is preferable. 3 More preferably, 350 kg / m 3 The above is more preferable. On the other hand, the total amount of binder is 800 kg / m 3 Less than 700kg / m is preferable. 3 Less than 600kg / m is preferable. 3 The following is preferred:

[0031] <<Grained blast furnace slag>> The binder contains at least ground granulated blast furnace slag. An example of the ground granulated blast furnace slag is ground granulated blast furnace slag for concrete as specified in JIS A 6206:2013.

[0032] "cement" The binder preferably further includes cement. Examples of cement include various types of cement such as ordinary Portland cement, ecocement, high-early-strength cement, and alumina cement. These various cements are strongly alkaline, and therefore can stimulate the ground granulated blast furnace slag with alkali, accelerating the hydration reaction rate of the ground granulated blast furnace slag. From the viewpoint of sufficiently stimulating the ground granulated blast furnace slag with alkali, the amount of cement mixed is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 10% by mass or more, based on the total mass of the ground granulated blast furnace slag. On the other hand, if the amount of cement is too large, the effect of the alkaline stimulation becomes saturated and it becomes uneconomical, so the amount of cement is preferably 45 mass% or less, more preferably 30 mass% or less, and even more preferably 20 mass% or less, based on the total weight of the ground granulated blast furnace slag.

[0033] Other Binders Other binders may also be used in the present manufacturing method, such as silica fume, fly ash, and the like. An example of silica fume is silica fume for concrete as specified in JIS A 6207:2011. The fly ash may be, for example, fly ash produced by coal-fired power generation, and is preferably fly ash for concrete as specified in JIS A 6201:2015 or fly ash powder.

[0034] <Mass ratio (fine steel slag aggregate / ground granulated blast furnace slag)> Next, the mass ratio of the steelmaking slag fine aggregate to the ground granulated blast furnace slag (steelmaking slag fine aggregate / ground granulated blast furnace slag) will be described. The mass ratio (fine steelmaking slag aggregate / ground granulated blast furnace slag) is preferably 1.5 or more, more preferably 1.8 or more, and even more preferably 2.0 or more. This makes it easier to form a strong transition body, improves the static elastic modulus, and improves the durability of the resulting hydrated solidified body.

[0035] The upper limit is not particularly limited. However, if the amount of ground granulated blast furnace slag is extremely small relative to the amount of fine steel slag aggregate, the strength of the hydrated solidified body is not easily achieved. Therefore, the mass ratio (fine steel slag aggregate / ground granulated blast furnace slag) is preferably 5.0 or less, more preferably 3.5 or less, and even more preferably 2.5 or less.

[0036] <water> The water used in the present production method is not particularly limited. However, it is preferable that the amount of water is as small as possible within the range in which the composition containing the above-mentioned components can be easily mixed. 3 Less than 210kg / m is preferable. 3 Less than 190kg / m is more preferable. 3 The following is even more preferred:

[0037] <Other Ingredients> In the present production method, other components may also be used. For example, in order to ensure the workability of the hydrated solidified body that has not yet hardened, admixtures such as water reducing agents that are commonly used in concrete may be used. When using admixtures, the mixing rate is 10 kg / m 3 Less than 7kg / m is preferable. 3 The following is more preferred:

[0038] <Mixing and curing> In this production method, a composition containing the above-mentioned components is kneaded, and the resulting kneaded product is hardened to obtain a hydrated solidified body. The blending amount of each component described above is the content in this composition. The mixing, pouring, molding, curing, etc., required for obtaining the hydrated solidified body may be the same as those for ordinary concrete or mortar. There is no particular restriction on the hardening.

[0039] Shatter After the kneaded mixture has hardened, the resulting hydrated solid may be crushed. For example, the hydrated solidified material is crushed to 2000 kg / piece or less. This allows the crushed hydrated solidified material to be used as a substitute for rubble or cover stone in port construction. Crushing to 2000 kg / piece or less also makes it easier to transport. The hydrated solidified material may also be crushed to 53 mm or less. This allows the crushed hydrated solidified material to be used as a roadbed material. Crushing the material to 53 mm or less improves compaction properties when used as a roadbed material. EXAMPLES

[0040] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the examples described below.

[0041] <Steel slag A-D> The calcium ion concentrations of the steelmaking slags A to D used in the following Invention Examples 1 to 12 and Comparative Examples 1 to 4 are shown in Table 1 below.

[0042] [Table 1]

[0043] As shown in Table 1 above, steelmaking slags A to C had calcium ion concentrations of 30 mg / L or more, and steelmaking slag D had a calcium ion concentration of less than 30 mg / L. As the steelmaking slags A to D, at least one of hot metal pretreatment slag and converter decarburization slag was used.

[0044] <Invention Examples 1 to 12 and Comparative Examples 1 to 4> Hydrated bodies were produced using any one of steelmaking slags A to D as the steelmaking slag fine aggregate and the steelmaking slag coarse aggregate. More specifically, the components (aggregate, binder, water, and water-reducing agent) shown in Table 2 below were mixed in the amounts shown in Table 2 below to prepare a composition, which was then kneaded using a mixer to obtain a kneaded mixture. The obtained kneaded product was cast into a cylindrical formwork of 100 mm in diameter and 200 mm in height, and after 24 hours, the formwork was removed and the product was cured in water at 20° C. In this way, the kneaded product was hardened to obtain a hydrated solidified body.

[0045] The steelmaking slag coarse aggregate used had a particle size of 25 mm or less. The ground granulated blast furnace slag used was ground granulated blast furnace slag for concrete (ground granulated blast furnace slag 4000) as specified in JIS A 6206:2013. As the ordinary Portland cement, ordinary Portland cement specified in JIS R 5210:2009 was used.

[0046] <evaluation> The hydrated solidified body was measured for compressive strength (unit: N / mm2) according to the method described in JIS A 1149:2017 "Test method for static elastic modulus of concrete" after 28 days of age (curing period: 28 days). 2 ) and static elastic modulus (unit: kN / mm 2 ) was measured. Furthermore, the ratio of the static elastic modulus to the compressive strength (static elastic modulus / compressive strength) was calculated. The larger the ratio (static elastic modulus / compressive strength), the more durable the hydrated solidified material was evaluated to be. The results are shown in Table 2 below.

[0047] [Table 2]

[0048] <Summary of evaluation results> The hydrated materials of Comparative Examples 1 and 2, in which steelmaking slag D was used as the steelmaking slag fine aggregate, had a ratio (static elastic modulus / compressive strength) of 695 or less. In addition, steelmaking slags A to C were used as fine steelmaking slag aggregates, and the mixing ratio of the steelmaking slag fine aggregates was 800 kg / m 3 The hydrated materials of Comparative Examples 3 and 4, which were less than 100%, had a ratio (static elastic modulus / compressive strength) of 697 or less. In contrast, steelmaking slags A to C were used as the steelmaking slag fine aggregate, and the mixing ratio of the steelmaking slag fine aggregate was 800 kg / m 3 The hydrated materials of Examples 1 to 12, which were as described above, had a ratio (static elastic modulus / compressive strength) of 771 or more, and were more durable than Comparative Examples 1 to 4.

[0049] Comparing Examples 1 to 12, the hydrated solidified body of Example 11, which has a mass ratio (fine steelmaking slag aggregate / ground granulated blast furnace slag) of 1.8, had a larger ratio (static elastic modulus / compressive strength) and better durability than the hydrated solidified body of the other Examples, which have a mass ratio (fine steelmaking slag aggregate / ground granulated blast furnace slag) of 2.0 or more.

[0050] <Mass production> Next, a large amount of hydrated solids were produced using the blends of Invention Examples 1 and 4.

[0051] Composition of Example 1 The hydrated solidified material, which was aged 2 days, was crushed into pieces of 1000-2000 kg / piece or 50-300 kg / piece using heavy machinery, and then further cured. When the hydrated solidified material, which was aged 28 days, was used as covering stone and rubble, it was found to have the same durability and workability as natural stone.

[0052] Composition of Invention Example 4 The hydrated solidified material, which was aged 2 days, was crushed to 100 kg or less using heavy machinery and then further cured. The hydrated solidified material, which was aged 28 days, was crushed to 53 mm or less using a jaw crusher and adjusted to the particle size range of CS-40 specified in JIS A 5015:2018 "Iron and steel slag for roads". When this crushed material was used as road base material, it was found to have the same durability and workability as road base materials using CS-40 or natural stone.

Claims

1. A composition containing an aggregate containing steelmaking slag, a binder containing ground granulated blast furnace slag, and water is kneaded and hardened to obtain a hydrated solidified body, The steelmaking slag includes a steelmaking slag fine aggregate, The steel slag fine aggregate has a calcium ion concentration of 30 mg / L or more in a test solution obtained by carrying out a "test using as-used" described in JIS K 0058-1:2005 "Testing methods for chemical substances of slags - Part 1: Testing method for elution amount"; The amount of the steel slag fine aggregate mixed is 800 kg / m 3 or more and 1500 kg / m 3 or less, A method for producing a hydrated solid, wherein a mass ratio of the fine steelmaking slag aggregate to the ground granulated blast furnace slag is 2.0 or more and 5.0 or less.

2. The method for producing a hydrated solidified body according to claim 1 , wherein the binder further comprises cement.

3. 3. The method for producing a hydrated solidified material according to claim 1, wherein the obtained hydrated solidified material is crushed to a mass of 2000 kg or less per piece.

4. 3. The method for producing a hydrated solidified material according to claim 1, wherein the obtained hydrated solidified material is crushed to a particle size of 53 mm or less.

Citation Information

Patent Citations

  • Road pavement slab using mill slag as raw material

    JP2001323403A

  • Underwater structure and its manufacturing method

    JP2006264045A

  • Elution amount testing method for slugs

    JP2012189416A

  • Steel-making slag concrete

    JP2013006743A

  • Method for producing hydrated matrix and hydrated matrix

    JP2014201497A